Pengaruh Penerapan Akuntansi Sektor Publik, Anggaran Berbasis Kinerja, Dan Good Governance Terhadap Akuntabilitas Kinerja Instansi Pemerintah Desa Pada Kecamatan Karanggede - Hesti Ria; Indra Lila Kusuma; Wikan Budi Utami (Jurnal Akuntansi dan Pajak, 2027)
This study aims to examine and analyze the effect of the implementation of public sector accounting, performance-based budgeting, and good governance on the performance accountability of village government agencies in Karanggede District. This study employed a quantitative approach with a survey method through the distribution of questionnaires to village government officials. The sample was determined using a purposive sampling technique, with 128 respondents. The data obtained were analyzed using multiple linear regression with the help of SPSS, through the stages of validity testing, reliability testing, classical assumption testing, t-tests, F-tests, and the coefficient of determination (R²) test. The results showed that partial or t-tests between the variables of public sector accounting implementation, performance-based budgeting, and good governance had a positive and significant effect on government agency performance accountability. This indicates that the better the implementation of public sector accounting, performance-based budget management, and the application of good governance principles, the greater the performance accountability of government agencies. Keywords: Public Sector Accounting, Performance-Based Budgeting, Good Governance, Government Agency Performance Accountability